2018
DOI: 10.3390/foods7040043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oregano Essential Oil and Aqueous Oregano Infusion Application on Microbiological Properties of Samarella (Tsamarella), a Traditional Meat Product of Cyprus

Abstract: Different types of dried meat products manufactured by different drying and curing methods are very common and well-known with a long history all over the world. Samarella (tsamarella) is one of these products and is famous among traditionally produced meat products in Cypriot gastronomy. The aim of this study was to investigate the effect of oregano essential oil (OEO) and aqueous oregano infusion (AOI) applications on the microbiological properties of samarella. In order to carry out this study, traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Oregano oil (Clive Tuebes, South Africa) was diluted to a concentration of 1% v/v in sterilised spring water. The concentration of 1% was chosen as previous research has indicated that it is organoleptically acceptable and can extend shelf life (Ulusoy, Hecer, Kaynarca, & Berkan, 2018). Prior to oregano oil treatment, the twelve vacuum packed black wildebeest BF muscles (left side) were defrosted at 2.6±0.6⁰C for 48 h, each black wildebeest BF muscle was cut into six steaks of 1.5 cm thickness and weighing approximately 150 grams.…”
Section: Oregano Oil Preparation and Meat Treatmentmentioning
confidence: 99%
“…Oregano oil (Clive Tuebes, South Africa) was diluted to a concentration of 1% v/v in sterilised spring water. The concentration of 1% was chosen as previous research has indicated that it is organoleptically acceptable and can extend shelf life (Ulusoy, Hecer, Kaynarca, & Berkan, 2018). Prior to oregano oil treatment, the twelve vacuum packed black wildebeest BF muscles (left side) were defrosted at 2.6±0.6⁰C for 48 h, each black wildebeest BF muscle was cut into six steaks of 1.5 cm thickness and weighing approximately 150 grams.…”
Section: Oregano Oil Preparation and Meat Treatmentmentioning
confidence: 99%
“…Oregano has been assessed for its antioxidant and antimicrobial characteristics with particular relevance to food preservation [10,11]. e popularized naturally preserved meat is samarella containing major fraction of oregano [12]. Moreover, oregano essential oil has been used as a major food additive in European Union for health benefits [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies where OEO has been added to preserve meat products. Levels of 0.002% (20 ppm) OEO have been included in the formulation of chicken meat (Al‐Hijazeen, Mendonca, Lee, & Ahn, ), 0.005% (50 ppm) in dry cured sausages (García‐Díez et al, ), 0.05% to 2% in poultry fillets (Kahraman et al, ), 10 to 100 ppm in Italian salami (Cenci et al, ), 0.25% (v/v) in poultry sausages (El Adab & Hassouna, ), 0.345% to 3.45% in fresh sausages (Busatta, Mossi, Rodrigues, Cansian, & Oliveira, ), 2% and 4% in packaged pork (Paparella et al, ), 5% in Cypriot samarella (Ulusoy et al, ), 0.5 to 2.0% w/v in broiler breast (Chaleshtori & Chaleshtori, ), and 1.5 to 6 ml in dried meat (Hernández et al, ). These reports showed that concentrations of OEO lower than 1% were successful to inhibit microbial growth without affecting the sensory quality of the products.…”
Section: Resultsmentioning
confidence: 99%
“…This is how OEO has been used in the present study as a natural antioxidant (Benavides, Villalobos-Carvajal, & Reyes, 2012) and it confers attraction to foods. The latter is due to the fact that the smell and taste of oregano oil has sweet and fruity de- to 2% in poultry fillets (Kahraman et al, 2016), 10 to 100 ppm in Italian salami (Cenci et al, 2015), 0.25% (v/v) in poultry sausages (El Adab & Hassouna, 2016), 0.345% to 3.45% in fresh sausages (Busatta, Mossi, Rodrigues, Cansian, & Oliveira, 2007), 2% and 4% in packaged pork (Paparella et al, 2016), 5% in Cypriot samarella (Ulusoy et al, 2018), 0.5 to 2.0% w/v in broiler breast (Chaleshtori & Chaleshtori, 2017), and 1.5 to 6 ml in dried meat . These reports showed that concentrations of OEO lower than 1% were successful to inhibit microbial growth without affecting the sensory quality of the products.…”
Section: Proximate Compositionmentioning
confidence: 99%
See 1 more Smart Citation